Considering the Impact of High School Sexual Education on Past Sexual Victimization and Rape Myth Acceptance in a College Sample - Caulfield, Nicole M. (Journal of interpersonal violence, 2025)
Sexual victimization is a serious public health crisis affecting college students, with high rates reported among both women and men. Sexual consent education is crucial as it defines sexual assault and is linked to reduced risk of victimization. Rape myths and stereotyped beliefs shifting blame to survivors are established risk factors for sexual violence. Comprehensive sexual education can mitigate these attitudes, fostering a supportive environment for survivors. However, most high school students in the United States receive abstinence-based or abstinence-plus education, which uses unstandardized protocols and often lacks information about sexual consent. The following study explores the influence of high school sexual education on past sexual victimization and rape myth acceptance in college students. Six hundred sixty-four undergraduate students participated in an online survey through a university participant pool. Results show that those who received comprehensive sexual education were more likely to understand sexual consent and were less likely to endorse past sexual victimization. In contrast, students without comprehensive sexual education reported lower satisfaction with their sexual education and greater acceptance of rape myths. Despite limitations in the study’s sample and reliance on self-reporting, this research highlights the importance of implementing comprehensive sexual education, including consent education, in high schools. Policymakers and educators must recognize the influence of comprehensive sexual education in promoting healthy relationships and combating sexual assault. As a significant public health concern, incorporating standardized sexual consent education into high school curricula can equip students with the knowledge and skills to make informed decisions about their sexual health and relationships. Future research should explore diverse populations and the mediating role of related factors that may further influence these relationships. These efforts will contribute to fostering a safer environment within educational institutions and combating sexual assault.